2016
DOI: 10.1021/acscatal.6b02794
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active, CO-Tolerant, and Robust Hydrogen Anode Catalysts: Pt–M (M = Fe, Co, Ni) Alloys with Stabilized Pt-Skin Layers

Abstract: The electrocatalytic activity for the hydrogen oxidation reaction (HOR) in the presence of 1000 ppm of CO has been investigated on a series of binary Pt alloy catalysts Pt–M (M = Fe, Co, Ni), having two atomic layers of stabilized Pt skin (Pt2AL), supported on carbon black (Pt2AL–PtFe/C, Pt2AL–PtCo/C, and Pt2AL–PtNi/C) in 0.1 M HClO4 solution at 70 and 90 °C. It was found that Pt2AL–PtFe/C exhibited the highest CO-tolerant HOR activity (with respect to the area-specific activity j s and the mass activity MA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 44 publications
2
60
0
Order By: Relevance
“…It is well known that the CO coverage and/or adsorption strength on Pt and Pt alloys depend upon various structural and electronic factors. This has been documented experimentally and theoretically in previous papers, for pure Pt, and for Pt-M alloys, [42][43][44][45] and thus, it has been found that the apparent CO coverage on Pt and Pt-M surfaces (θ, %) does not always reach 100%. [37][38][39][40][41] Therefore, in the present work, we have simply compared the catalytic behavior among them based on the Pt weight, or the geometric electrode surface area of the RDE, and the MEAs loaded with the same amounts of Pt.…”
Section: Resultssupporting
confidence: 58%
“…It is well known that the CO coverage and/or adsorption strength on Pt and Pt alloys depend upon various structural and electronic factors. This has been documented experimentally and theoretically in previous papers, for pure Pt, and for Pt-M alloys, [42][43][44][45] and thus, it has been found that the apparent CO coverage on Pt and Pt-M surfaces (θ, %) does not always reach 100%. [37][38][39][40][41] Therefore, in the present work, we have simply compared the catalytic behavior among them based on the Pt weight, or the geometric electrode surface area of the RDE, and the MEAs loaded with the same amounts of Pt.…”
Section: Resultssupporting
confidence: 58%
“…Such an enhancement factor in the MA for the HOR of pure H2 on the Pt2AL-PtFe/C was smaller than that (ca. 2.5 times) measured in the CFE at 70 and 90 °C [10]. This is ascribed with certainty to the fact that it is difficult for all of the catalyst particles to work effectively for the HOR, because the thickness of the catalyst layer loaded on the ATR prism corresponded to about 6.5 monolayers of the carbon black particles (to increase the signal/noise ratio of the IR spectrum), whereas the amount of the catalyst loaded in the CFE cell was ca.…”
Section: Introductionmentioning
confidence: 93%
“…They showed superlative CO-tolerance and high robustness with respect to air exposure at 70 to 90°C. 54,55 The Pt xAL -PtFe/C catalyst exhibited the highest CO-tolerant HOR activity ( j s and MA), followed by Pt xAL -PtCo/C and Pt xAL -PtNi/C. In situ ATR-FTIR, 22 in situ X-ray absorption spectroscopy, 118 and DFT calculations 55 clearly demonstrated the weakening of CO adsorption on the Pt xAL .…”
Section: Co-tolerant Hor Mechanism At Pt-alloysmentioning
confidence: 90%
“…Recently, non-fluorinated hydrocarbon (HC) electrolyte membranes have been developed to reduce cost, to elevate the operating temperature, and to avoid environmental pollution due to fluoride on disposal. Specifically, the elevation of operating temperature (² 100°C) leads to a significant cost reduction by increases in the MA values for the ORR 40 of the cathode catalysts and the CO-tolerant HOR of the anode catalysts, 36,55 together with a down-sizing of the heat exchanger (radiator) in FCVs (due to increased ¦T ).…”
Section: Cathode Catalyst Layers With Sulfonated Hydrocarbonmentioning
confidence: 99%
See 1 more Smart Citation